Το συναξάρι του Γένους - Σαρδελής, Κώστας, 1932- (Ελληνικό Βιβλίο, 1969)
Διονύσιος ο Σκυλόσοφος -- Σεραφείμ Φαναρίου -- Μελέτιος Πηγάς -- Κύριλλος Λούκαρης -- Ηλίας Μηνιάτης -- Ευγένιος Γιαννούλης ο Αιτωλός -- Αναστάσιος Γόρδιος -- Θεόκλητος Πολυειδής -- Χρύσανθος ο Αιτωλός -- Ευγένιος Βούλγαρης -- Σεραφείμ Β΄ ο Γενάρχης -- Ρήγας Βελεστινλής -- Γρηγόριος ο Ε΄ Νικόδημος ο Αγιορείτης -- Ανθημος Γαζής -- Κωνσταντίνος Κούμας -- Καπετάν Καλόγηρος